Development patterns of necrophagous flies infesting rabbit carcasses decomposing in Mount Kapur Cave and its surrounding primary forest in Kuching, Sarawak - Nordin, N. H.; Ahmad, U. K.; Rabbit, Abdul; Kamaluddin, M. R.; Ismail, D.; Muda, N. W.; Wahab, Abdul R.; Mahat, N. A. (Malaysian Soc Parasitology Tropical Medicine, 2024)
Indexed by WOS/ Scopus